Formula Switch Leads to Enteral Feeding Tolerance Improvements in Children With Developmental Delays - Gerard Minor MMS, PA-C; Juan B. Ochoa MD; Heidi Storm MS, RD; Seletha Periman MS, MPH, RD (SAGE Publishing, 2016)
Background: Children with developmental delays are often dependent on enteral nutrition. The aim of our study was to evaluate improvement in tolerance parameters in these children who were switched from an intact protein formula to a 100% whey, peptide-based formula. Methods: A retrospective chart review of children with developmental delays who were failing to reach adequate nutritional goals on standard polymeric formulas were switched to a 100% whey peptide-based formula. Enteral volume goals, caloric goals, and change in medication used to improve feeding tolerance were assessed before and after formula switch. Results: Medical records of 13 children (aged 8.4 ± 4.6 years) met criteria. All children had a primary diagnosis of developmental delay, and 77% were fed via gastrostomy tube. Of the 13 children assessed, 92% experienced improved feeding tolerance, and 75% of these reported the time to improvement within 1 week after formula switch. Feeding tolerance parameters that improved were vomiting (86%), gagging and retching (75%), high residual volumes (63%), constipation (43%), diarrhea (100%), and poor weight gain (100%). Conclusion: Switching to a 100% whey, peptide-based formula improved symptoms of feeding intolerance in the majority of these developmentally delayed children.